COMPUTATIONAL AND WATER ELECTROLYSIS STUDY OF 5,10,15,20-TETRAKIS(3-HYDROXYPHENYL)-PORPHYRIN - TUDORAN, Marina Alexandra; TARANU, Bogdan-Ovidiu (Studia Universitatis Babeș-Bolyai Chemia, 2026)
The free-base, symmetrically substituted 5,10,15,20-tetrakis(3-hydroxyphenyl)-porphyrin was the subject of a study combining computational and experimental analysis, with an emphasis on the molecule’s water-splitting electrocatalytic characteristics. Ab initio and DFT methods were used to investigate the porphyrin’s structural and electronic properties. The water-splitting experiments, performed in solutions with different pH values, were carried out with porphyrin-based electrodes that were modified using different strategies. The electrode manufactured by drop-casting a catalyst ink containing the porphyrin and carbon black on a graphite substrate displayed an overpotential value for the oxygen evolution reaction of 0.595 V vs. RHE and a Tafel slope of 0.337 V/dec in a neutral environment. Data acquired during the electrochemical experiments were used to perform statistical analysis. The correlation analysis indicated a significant association between pH and overpotential. The combined study improves the current scientific understanding of the porphyrin’s properties and shows the effect of the electrode modification strategies on its water-splitting electrocatalytic activity. The Supplementary Material file can be downloaded at: https://doi.org/10.5281/zenodo.20571954